Prediction accuracy of IOL calculation formulas using the ASCRS online calculator for a diffractive extended depth-of-focus IOL after myopic laser in situ keratomileusis. Issue 9 (September 2020) - Lwowski, Christoph; Pawlowicz, Katarzyna; Hinzelmann, Lisa; Adas, Mahmoud; Kohnen, Thomas
Abstract : Calculating diffractive EDOF IOLs in lens surgery in post-LASIK of myopic eyes reached best results when using the average of all formulas or the Shammas and Haigis-L formulas. Abstract : Background: To evaluate IOL calculation formulas provided by an online calculation tool from the ASCRS for an extended depth-of-focus (EDOF) IOL after previous myopic laser in situ keratomileusis (LASIK). Setting: Department of Ophthalmology, Goethe University, Frankfurt, Germany. Design: Retrospective consecutive case series. Methods: Patients who underwent cataract surgery or refractive lens exchange with implantation of a diffractive EDOF IOL and who had a history of myopic LASIK were included. Biometry, refractive data regarding the LASIK procedure, target refraction, and postoperative refraction were collected. Mean prediction error, mean absolute error (MAE), and the number of eyes within ±0.5 diopters (D), ±1.0 D, ±1.5 D, and ±2.0 D were calculated with the following formulas from the ASCRS calculator: Shammas, Haigis-L, Barrett True-K, Barrett No History, Masket, modified Masket, and the average of all formulas (average). Results: Twenty-five eyes matched the inclusion criteria. Mean spherical equivalent (SE) was −0.81 ± 0.69 D; the mean pre-LASIK SE was −6.4 ± 3.63 D. The formulas ranked by MAE were Shammas (0.7 ± 0.75 D), Haigis-L (0.72 ± 0.57 D), average (0.79 ± 0.8 D), Barrett True-K (1.14 ± 0.89 D), modified Masket (1.4 ± 1.15 D), Barrett No History (1.45 ± 0.7D ), and Masket (1.64 ± 1.27 D). The formulas with the most eyes within ±0.5 D were average (52%), Shammas (48%), and Haigis-L (44%) formulas. Conclusions: Calculation of IOLs in eyes with a history of refractive surgery remains a challenge. In this study, the Shammas and Haigis-L formulas performed best regarding MAE and percentage of eyes within ±0.5 D; however, the average of all formulas delivered reasonable results.